Impacts of Salmonid Fish Production on River Water Quality: A Critical Appraisal of the Evidence - Anna N. S. Michalopoulou; Nic R. Bury; Robert A. Holland; Imogen Speck; Tim Sykes; Gail Taylor; Marc G. Dumont; Kelvin S.‐H. Peh (Reviews in Aquaculture, 2026)
Rivers are recognised as providing valuable goods and services to society, and as hotspots of global biodiversity. Fish farming is an economically important activity associated with river systems; however, the effects of this industry on river health are not entirely understood. Studies evaluating interactions between freshwater fish farms and rivers are limited; therefore, we conducted a systematic review and an appraisal of evidence quality to assess the impacts of salmonid fish farming on river water quality. The review revealed that two main types of water quality indicators are generally applied: physicochemical and biological. The response variables used to determine the effects of fish farm effluent on water quality vary considerably, yet most studies indicate that aquaculture negatively affects the environment. Overall, we highlight the knowledge gaps, including a lack of studies in freshwater aquaculture hotspots. The effects of fish farming on bacterial communities are also not clear due to limited research on these bioindicators. We suggest improvements in study design, including thorough consideration of confounding factors, and the provision of background information on the fish farms.